Integrated analysis of somatic mutations and focal copy-number changes identifies key genes and pathways in hepatocellular carcinoma - Guichard, Cécile; Amaddeo, Giuliana; Imbeaud, Sandrine; Ladeiro, Yannick; Pelletier, Laura; Maad, Ichrafe Ben; Calderaro, Julien; Bioulac-Sage, Paulette; Letexier, Mélanie; Degos, Françoise; Clément, Bruno; Balabaud, Charles; et al. (Nature genetics, 2012)
Jessica Zucman-Rossi and colleagues report exome sequencing of 24 hepatocellular carcinomas and non-tumor liver tissues and copy-number analysis of 125 tumors. They identify new recurrent mutations in ARID1A , RPS6KA3 , NFE2L2 and IRF2 in HCC. Hepatocellular carcinoma (HCC) is the most common primary liver malignancy. Here, we performed high-resolution copy-number analysis on 125 HCC tumors and whole-exome sequencing on 24 of these tumors. We identified 135 homozygous deletions and 994 somatic mutations of genes with predicted functional consequences. We found new recurrent alterations in four genes ( ARID1A , RPS6KA3 , NFE2L2 and IRF2 ) not previously described in HCC. Functional analyses showed tumor suppressor properties for IRF2 , whose inactivation, exclusively found in hepatitis B virus (HBV)-related tumors, led to impaired TP53 function. In contrast, inactivation of chromatin remodelers was frequent and predominant in alcohol-related tumors. Moreover, association of mutations in specific genes ( RPS6KA3 - AXIN1 and NFE2L2 - CTNNB1 ) suggested that Wnt/β-catenin signaling might cooperate in liver carcinogenesis with both oxidative stress metabolism and Ras/mitogen-activated protein kinase (MAPK) pathways. This study provides insight into the somatic mutational landscape in HCC and identifies interactions between mutations in oncogene and tumor suppressor gene mutations related to specific risk factors.